Pengaruh Tunjangan Kinerja dan Penempatan Kerja Terhadap Motivasi Kerja Tenaga Kependidikan Pada Politeknik Pertanian Payakumbuh Dengan Kepuasan Kerja Sebagai Variable Moderating - Isnanda; Sabri; Putri, Anne; nasfi, nasfi (El-kahfi | Jurnal Ekonomi Islam, 2022)
The purpose of this study is to analyze the effect of performance allowances on the work motivation of educators, the effect of job placement on the work motivation of educators, the effect of job satisfaction on the work motivation of educators, the effect of performance allowances on the job satisfaction of educators, the effect of job placement on the job satisfaction of educators. , the effect of job satisfaction mediates the relationship between performance allowances and the work motivation of educators and the effect of job satisfaction mediates the relationship between placement and work motivation of educators. The object of research is Payakumbuh State Agricultural Polytechnic education staff. The study used the census method, where the population of 176 education personnel was also used as the research sample. Data collection techniques using questionnaires/questionnaires and documentation methods, motivation variable (Y) as dependent variable (dependent), performance allowance (X1), job placement (X2) and job satisfaction (M) as independent variable, with management research data using Smart PLS 3.2.7 Software.